PENGARUH HINDU DALAM MITOS PADI DI JAWA - Rita Istari (BRIN, 2005)
The concept of Mother Goddess in agricultural culture, namely equating or identifying Mother Goddess with soil, plants needed by humans and considered to be born by Mother Goddess. As for the main reason for the worship of Mother Goddess, first of all was the emergence of a feeling of amazement, wonder and human ignorance of natural processes, namely about the secret of birth, the secret of the origin of human or animal life. Their way of thinking which is still very simple then looks for the sources of the cause, and in the end the choice falls to the female character or the mother, because it is based on the experience that it is the woman who gives birth.